Directrices para la implementación de buenas prácticas de manufactura para el aseguramiento de la calidad de productos cosméticos naturales (2021)
Good manufacturing practices (GMP) are a basic and useful tool for obtaining safe products for human consumption, their implementation in manufacturing processes contributes to controlling hygiene and handling of these, minimizing in each process stage risks and ensuring quality. The main objective of this work is to provide guidelines for the implementation of good manufacturing practices to ensure the quality of natural cosmetic products. Consequently, the article reviews the literature on Good Manufacturing Practices in the cosmetic sector, reviews the importance and benefits of natural cosmetics and analyzes the current state of the conventional cosmetic industry compared to natural cosmetics in the country, as well as the current and applicable legislation. In the process for quality assurance of natural cosmetic products and according to the data collected, guidelines are developed for the implementation of good manufacturing practices.